Experimental and Numerical Study of Submerged Inclined Buoyant Jet Discharges into Stagnant Saline Ambient Water - Guo, Yilin (Université d'Ottawa / University of Ottawa, 2020)
Treated and untreated liquid that is discharged from industrial and desalination plants is one of the main factors that break the ecological balance and destroys aquatic habitat in lakes, rivers and coastal areas where the effluent is discharged. Positively and negatively buoyant jets are two categories of outfalls which are generated because of the destiny difference between the effluent and ambient fluid. In order to ensure minimal impact of the effluent on the environment, it is necessary to estimate the dilution of the jet and compare it with environmental regulations on the level of required dilution to ensure that the concentration of the effluent is diluted quickly enough and the concentration of the effluent at different points does not exceed the allowed concentrations. This study investigated the positively buoyant jet, which happens near the coastal and near water area. For instance, cooling water that flows out from a power plant or factory, wasted water that is discharged from an industrial plant near river, submerged drainage from civil municipal sewer systems and treated water from desalination plant in coastal area. Density difference, velocity and inclined angle of the jet were considered as the main factors that contribute to the jet spreading and were compared to develop the best solution for its dilution. The jet was discharged inclined downward to allow for more mixing and dilution of the effluent with the ambient water. In order to simulate a positive jet, tap water was injected in saline ambient. A large number of experiments were conducted in the laboratory and using camera imaging. The jet trajectory was estimated from the images using image processing and the impact of various parameters such as Froude number and jet velocity were investigated. The opensource software OpenFOAM, was employed for numerical simulations which is a finite volume model ensures mass conservation and allows for flexible mesh size for further accuracy and optimization of computational cost. Using this Computational Fluid Dynamics (CFD) model, the numerical simulations were performed, and the results were compared with laboratory experiments. A Reynold-Averaged Navier-Stokes (RANS) approach was employed in the numerical simulations which offers a good balance between accuracy and computational cost. It was found that the numerical model in conjunction with the second order turbulence model called Launder-Reece- Rodi model (LRR) had a reasonable agreement with the experimental data.
Keywords: Positively buoyant jet; Inclined jet; Experimental study; Numerical study; OpenFOAM